2021
DOI: 10.1177/09612033211005085
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of digital and non-digital non-pharmacological interventions that target quality of life and psychological outcomes in adults with systemic lupus erythematosus

Abstract: Background Patients with systemic lupus erythematous (SLE) experience psychological comorbidities and impaired quality of life (QOL). We conducted a systematic review to examine the efficacy of non-pharmacological interventions for improving psychological outcomes and/or QOL in patients with SLE. To expand on a previous systematic review in this area and enhance our understanding of efficacious interventions for this population, our search included quasi-experimental and experimental studies of interventions d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…We found a statistically beneficial effect favoring exercise intervention with a medium effect size of 0.468. This finding agrees with previous systematic reviews of non-pharmacological interventions, including exercise, that it could improve quality of life in patients with SLE [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found a statistically beneficial effect favoring exercise intervention with a medium effect size of 0.468. This finding agrees with previous systematic reviews of non-pharmacological interventions, including exercise, that it could improve quality of life in patients with SLE [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 92%
“…Another recent systematic review of 21 randomized controlled trials and two quasi-experimental studies in patients with SLE concluded that non-pharmacological interventions as an adjunct to usual medical care might be beneficial for improving patients’ quality of life and psychological outcomes. The interventions included two diet-based interventions, four psychological interventions, six physical activity interventions, and one self-management course [ 14 ]. Nevertheless, no meta-analysis assessing the effect of exercise on quality of life in patients with SLE is yet available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonpharmacological interventions (eg, psychological, educational interventions) delivered remotely and in person have shown promise to improve QoL and psychological outcomes in patients with lupus (5). Acceptance and commitment therapy (ACT) is one therapeutic option that may be particularly well suited for the needs of patients with SLE.…”
Section: Introductionmentioning
confidence: 99%
“…To prevent flare-ups or the exacerbation of lupus symptoms, a combination of medication treatments (e.g., antimalarials, glucocorticoids, and immunosuppressive agents) [ 15 , 16 ] and lifestyle changes (e.g., adherence to the medication regime, diet, sun exposure limitation, and stress management) should be used [ 17 , 18 ]. Furthermore, physical exercise and psychological interventions have been shown to improve symptoms of fatigue, depression, pain, and quality of life among lupus patients [ 17 , 19 ].…”
Section: Introductionmentioning
confidence: 99%